2018
DOI: 10.1109/tip.2017.2756450
|View full text |Cite
|
Sign up to set email alerts
|

Frankenstein: Learning Deep Face Representations Using Small Data

Abstract: Abstract-Deep convolutional neural networks have recently proven extremely effective for difficult face recognition problems in uncontrolled settings. To train such networks, very large training sets are needed with millions of labeled images. For some applications, such as near-infrared (NIR) face recognition, such large training datasets are not publicly available and difficult to collect. In this work, we propose a method to generate very large training datasets of synthetic images by compositing real face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 69 publications
(135 reference statements)
0
58
0
Order By: Relevance
“…Aggressive data augmentation is, therefore, a must with CNN-based models. When trying to learn a CNN-based model from scratch, researchers typically augment the available training data by producing data variations with, e.g., geometric transformations, color modifications, addition of noise, and more recently also by synthesizing samples of artificial identities, as, for example, described in [13].…”
Section: A Learning Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive data augmentation is, therefore, a must with CNN-based models. When trying to learn a CNN-based model from scratch, researchers typically augment the available training data by producing data variations with, e.g., geometric transformations, color modifications, addition of noise, and more recently also by synthesizing samples of artificial identities, as, for example, described in [13].…”
Section: A Learning Strategiesmentioning
confidence: 99%
“…In this paper we address the problem of training CNNs with limited training data and strive to develop an effective CNN-based model for ear recognition. Existing approaches to CNN training with small amounts of training data typically include i) metric-learning approaches, where training is performed with image pairs (or even triplets) instead of single images [8], [9], ii) data augmentation techniques that in addition to geometric and color perturbations of the existing training data also include the generation of synthetic data samples [10], [11], [12], [13], and iii) using existing CNNs (trained for related recognition problems) as so-called "black-box" feature extractors, on top of which additional classifiers are trained and used for recognition [14]. Here, we build on these approaches and successfully develop a CNN model for ear recognition by exploring different strategies to network training, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Verification accuracy can be affected by the type of bounding box used. In addition, most recent face recognition and verification methods [35,31,33,5,10,34] use some kind of 2D or 3D alignment procedure [41,15,28,8]. All these variables can lead to changes in performance of deep networks.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis: Removing the confounding factor stress would aid in creating models that are more generalizable across datasets. Previous research has shown that laboratory collected datasets are too small and often fail to capture the complete distribution of the domain [18,28] present in the real world. These datasets are often plagued with unintentional correlational factors [27,28].…”
Section: Questionmentioning
confidence: 99%